Intracellular Antioxidant Activity of Grape Skin Polyphenolic Extracts in Rat Superficial Colonocytes: In situ Detection by Confocal Fluorescence Microscopy - Giordano, M. Elena; Ingrosso, Ilaria; Schettino, Trifone; Caricato, Roberto; Giovinazzo, Giovanna; Lionetto, M. Giulia (Frontiers in Physiology, 2016)
Colon is exposed to a number of prooxidant conditions and several colon diseases are associated with increased levels of reactive species. Polyphenols are the most abundant antioxidants in the diet, but to date no information is available about their absorption and potential intracellular antioxidant activity on colon epithelial cells. The work was addressed to study the intracellular antioxidant activity of red grape polyphenolic extracts on rat colon epithelium experimentally exposed to prooxidant conditions. The experimental model chosen was represented by freshly isolated colon explants, which closely resemble the functional and morphological characteristics of the epithelium in vivo. The study was carried out by in situ confocal microscopy observation on CM-H2DCFDA charged explants exposed to H2O2 (5, 10 and 15 min). The qualitative and quantitative polyphenolic composition of the extracts as well as their in vitro oxygen radical absorbing capacity (ORAC) was determined. The incubation of the explants with the polyphenolic extracts for 1h produced a significant decrease of the H2O2 induced fluorescence. This effect was more pronounced following 15 min H2O2 exposure with respect to 5 min and it was also more evident for extracts obtained from mature grapes, which showed an increased ORAC value and qualitative peculiarities in the polyphenolic composition. The results demonstrated the ability of red grape polyphenols to cross the plasma membrane and exert a direct intracellular antioxidant activity in surface colonocytes, inducing a protection against pro-oxidant conditions. The changes in the polyphenol composition due to ripening process was reflected in a more effective antioxidant protection.